2018
DOI: 10.1002/nag.2855
|View full text |Cite
|
Sign up to set email alerts
|

SANISAND‐FN: An evolving fabric‐based sand model accounting for stress principal axes rotation

Abstract: Summary SANISAND is the name of a family of bounding surface plasticity constitutive models for sand within the framework of critical state theory, which have been able to realistically simulate the sand behavior under conventional monotonic and cyclic loading paths. In order to incorporate the important role of evolving fabric anisotropy, one such model was modified within the framework of the new anisotropic critical state theory and named SANISAND‐F model. Yet the response under continuous stress principal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 53 publications
1
59
0
Order By: Relevance
“…It is important to notice that the DEM results are accommodated by the premises of ACST in a general descriptive way, based on how the basic entities of the theory are defined by those results, but no exact simulation by a constitutive model within ACST was made nor was it intended to be made, because no full constitutive formulation is provided. Equations and are fundamental equations of ACST and together with the generic constitutive Equations and can be incorporated in various specific constitutive modeling approaches within ACST, as for example in the SANISAND‐FR (Papadimitriou et al) and SANISAND‐FN (Petalas et al) models.…”
Section: Interpretation Of Dem Results Within Acstmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to notice that the DEM results are accommodated by the premises of ACST in a general descriptive way, based on how the basic entities of the theory are defined by those results, but no exact simulation by a constitutive model within ACST was made nor was it intended to be made, because no full constitutive formulation is provided. Equations and are fundamental equations of ACST and together with the generic constitutive Equations and can be incorporated in various specific constitutive modeling approaches within ACST, as for example in the SANISAND‐FR (Papadimitriou et al) and SANISAND‐FN (Petalas et al) models.…”
Section: Interpretation Of Dem Results Within Acstmentioning
confidence: 99%
“…Based on this new ingredient, it was possible to interpret during the aforementioned 3D DEM experiment the stress‐strain results by combining the DEM findings for the fabric‐related quantities with the basic equations proposed in ACST, thus, proving its relevance not only in regard to CS but also in relation to the response before and after CS is reached. In addition, this FAV A proved to be invaluable in simulating strongly anisotropic granular material response (eg, Yoshimine et al) as firstly shown by Li and Dafalias and sequentially by a number of ACST‐based constitutive models (eg, Papadimitriou et al, Petalas et al).…”
Section: Discussionmentioning
confidence: 99%
“…Note that a recently published new version of Sanisand [Petalas et al, 2019] is able to predict the measured contractant behavior in the hollow cylinder test of Figs. 20 to 24.…”
Section: Variations In Strain Components With Number Of Cyclesmentioning
confidence: 99%
“…However, this equation has a shortcoming, especially under the drained condition. Petalas et al [22] pointed out that during the simulation of drained PSR loading, if the sample is initially denser than critical, the value of b (already being larger than ) will increase due to its dependence on the state parameter (14) where h 0r and r are new model parameters associated with the PSR. In order to make K pr more sensitive to the stress ratio, r is usually larger than unity.…”
Section: The Modified Psr Soil Modelmentioning
confidence: 99%